ANALISIS KINERJA KEUANGAN PADA PERUM PEGADAIAN SYARIAH KANTOR CABANG BANDA ACEHTAHUN 2016-2018 - Zulkifli Umar; Maya Agustina; Bachyul Saputra (Asosiasi Dosen dan Praktisi Ekonomi Nusantara, 2024)
The purpose of this study is to describe and analyze the Financial Performance of Perum Pegadaian Syariah Banda Aceh Branch Office in 2016-2018. This research is classified as descriptive qualitative research. Data analysis is carried out by an analysis method that compares the theoretical review with the results of the research obtained, then draws conclusions and gives suggestions. The results of the study show that from the current ratio at PT. Pegadaian (Persero) Banda Aceh from 2016 to 2018 with inefficient financial performance capabilities. Quick ratio at PT. Pegadaian (Persero) Banda Aceh in 2016 can be said to be efficient, then in 2017 with a level of financial performance capability that is still very efficient and then in 2018 with a level of efficient financial performance capability. Gros profit margin at PT. Pegadaian (Persero) Banda Aceh from 2016 to 2018 with very efficient financial performance capabilities. Net profit margin at PT. Pegadaian (Persero) Banda Aceh from 2016 with very efficient financial performance capabilities and then in 2017 and 2018 with an efficient level of financial performance capabilities